Magnetic colloidal single particles and dumbbells on a tilted washboard moiré pattern in a precessing external field - Farrokhzad, Farzaneh; Stuhlmüller, Nico C. X; Ku wik, Piotr; Urbaniak, Maciej; Stobiecki, Feliks; Akhundzada, Sapida; Ehresmann, Arno; de las Heras, Daniel; Fischer, Thomas M (Soft matter, 2024)
We measure the dynamical behavior of colloidal singlets and dumbbells on an inclined magnetic moiré pattern, subject to a precessing external homogeneous magnetic field. At low external field strength single colloidal particles and dumbbells move everywhere on the pattern: at stronger external field strengths colloidal singlets and dumbbells are localized in generic locations. There are however nongeneric locations of flat channels that cross the moiré Wigner Seitz cell. In the flat channels we find gravitational driven translational and non-translational dynamic phase behavior of the colloidal singlets and dumbbells depending on the external field strength and the precession angle of the external homogeneous magnetic field. We measure the dynamical behavior of colloidal singlets and dumbbells on an inclined magnetic moiré pattern, subject to a precessing external homogeneous magnetic field.